The Influence of E-learning Applications on the Learning Outcomes of MA Muhammadiyah Nanahure Students - Nur Cahya Ninsih; Katharina Woli Namang; Alitalia Indah Sari; Susi Susanti Adang; Nurul Adnan Pertiwi (Journal of English Language and Education, 2026)
The development of information technology has brought significant changes to the world of education, one of which is the use of e-learning applications in the learning process. This study aims to examine and analyze the impact of e-learning application use on student learning outcomes at MA Muhammadiyah Nanahure. This article uses a literature review approach, reviewing various scientific research findings from the last five years (2020–2025) relevant to the topic of e-learning and student learning outcomes. The study results indicate that the implementation of e-learning applications generally has a positive impact on improving student learning outcomes, including cognitive aspects, learning motivation, and learning independence. Specific findings from the literature indicate an average increase in cognitive learning outcomes of up to 15-20% and a significant strengthening of student learning independence scores through the use of a Learning Management System (LMS). Factors influencing the success of e-learning include the quality of digital learning design, teacher competence in managing online learning, and the availability of supporting facilities and infrastructure. With proper management, e-learning can be an effective and relevant learning solution for implementation at MA Muhammadiyah Nanahure.